Public Debt, Global Governance and Economic Dynamism 2013
DOI: 10.1007/978-88-470-5331-1_12
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Multipliers and Public Debt Dynamics in Consolidations

Abstract: The success of a consolidation in reducing the debt ratio depends crucially on the value of the multiplier, which measures the impact of consolidation on growth, and on the reaction of sovereign yields to such a consolidation. We present a theoretical framework that formalizes the response of the public debt ratio to fiscal consolidations in relation to the value of fiscal multipliers, the starting debt level and the cyclical elasticity of the budget balance. We also assess the role of markets confidence to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 58 publications
0
41
0
3
Order By: Relevance
“…This choice is predicted by the desire to isolate the effect from the business cycle to the primary balance and exclude the effect from the primary balance to the business cycle. Boussard et al (2012) find that the latter effect can be substantial, in which case ordinary fixed effect estimations would presumably lead to lower estimates of the cyclical reaction. This is indeed the case as illustrated in Table B.1 in Appendix B where the results of estimating (1) using ordinary fixed effect least squares are presented.…”
Section: Ea12mentioning
confidence: 86%
See 1 more Smart Citation
“…This choice is predicted by the desire to isolate the effect from the business cycle to the primary balance and exclude the effect from the primary balance to the business cycle. Boussard et al (2012) find that the latter effect can be substantial, in which case ordinary fixed effect estimations would presumably lead to lower estimates of the cyclical reaction. This is indeed the case as illustrated in Table B.1 in Appendix B where the results of estimating (1) using ordinary fixed effect least squares are presented.…”
Section: Ea12mentioning
confidence: 86%
“…The rate of economic growth over the last four quarters, G4Y, may be affected by the fiscal stance in the four quarters "covered" by the variable. Indeed, studies suggest that fiscal policy is effective, albeit to varying degrees, in all EU countries (Boussard et al 2012).…”
Section: Specification Of Quarterly Reaction Functionmentioning
confidence: 99%
“…For a full discussion on this issue, see Buiter and Rahbari [36]. 29 This conclusion is also confirmed by the European Commission [42]; see also Boussard et al [43]. 30 In fact, at the end of 2014, TARGET2 imbalances were higher than their pre-crisis level; but they could reflect both the ordinary working of a monetary union where some peripheral countries are experiencing a slower recovery compared to core countries and the contagion effect connected with the new Greek political crisis.…”
Section: The Need Of a Lender Of Last Resortmentioning
confidence: 70%
“…While a comprehensive literature review can be found in Boussard, Castro, and Salto (2012), we shall recall here some of the most relevant contributions.…”
Section: Introductionmentioning
confidence: 99%